ChemInform Abstract: Synthesis, Structure, and Bonding of the Hexagonal Form of the Oxide Carbide ScAlOC. Issue 11 (18th March 2014) - Schultz, Peter; Sagawe, Vanessa; Hillebrecht, Harald
Abstract Red single crystals of the title compound are obtained by reaction of scandium, carbon, and an excess of aluminium (corundum crucible, 1820 °C, 60 s).